GIL: a Software Tool for the Construction of Information Dissemination Systems - Campos, João P. (1999)
Push-based delivery has motivated a growing interest, allowing dissemination of information to a large set of users, both in wired and wireless environments. In this paper, we present GIL, a software tool to automate the development process of information dissemination applications, which run on top of Ubidata, our software framework for mobile computing. GIL makes the channel definition and creation an easy task, even for non-technicians